The Use of Process and Output Controls in Foreign Markets - Gencturk, Esra F.; Aulakh, Preet S. (Journal of International Business Studies, 1995)
This study builds upon previous control research to propose a model of formal controls used in managing activities performed in foreign markets. Theoretically derived contingency relationships are also proposed to assess the performance consequences of different formal control types. The findings support the importance of internal and external sources of uncertainty in determining the type of control used. Partial support was also found for the premise that the fit between the type of control used and the type of uncertainty perceived will contribute to superior performance.